A review on Internet of Things (IoT), Internet of Everything (IoE) and Internet of Nano Things (IoNT) - Miraz, Mahdi H.; Ali, Maaruf; Excell, Peter S.; Picking, Rich (2015 Internet Technologies and Applications (ITA), 2015)
The current prominence and future promises of the Internet of Things (IoT), Internet of Everything (IoE) and Internet of Nano Things (IoNT) are extensively reviewed and a summary survey report is presented. The analysis clearly distinguishes between IoT and IoE which are wrongly considered to be the same by many people. Upon examining the current advancement in the fields of IoT, IoE and IoNT, the paper presents scenarios for the possible future expansion of their applications.